2019
DOI: 10.1556/2054.2019.029
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelics and potential benefits in “healthy normals”: A review of the literature

Abstract: We are in the midst of a psychedelic research renaissance. With research examining the efficacy of psychedelics as a treatment for a range of mental health indications still in its early stages, there is an increasing body of research to show that careful use of psychedelics can yield a variety of benefits in “healthy normals” and so lead to “the betterment of well people.” Psychedelics have been found to modulate neuroplasticity, and usage in a supportive setting can result in enduring increases in traits such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 83 publications
1
23
0
1
Order By: Relevance
“…The experience of awe has been linked to enhanced well-being ( Anderson et al, 2018b ; Dong and Ni, 2019 ; Rudd et al, 2012 ), life satisfaction ( Rudd et al, 2012 ), prosociality ( Bai et al., 2017 ; Piff et al, 2015 ; Sturm et al, 2020 ), and reduced negative affect ( Lopes et al, 2020 ), and mental distress ( Sturm et al, 2020 ), in addition to being associated with nature relatedness ( Bethelmy and Corraliza, 2019 ) and pro-environmental behaviour ( Wang and Liu, 2019 ; Zhao et al, 2018 ), all enduring effects associated with psychedelic use ( Gandy, 2019 ). Psychedelics have been found to elicit feelings of awe ( Griffiths et al, 2006 ; Hendricks, 2018 ; Noorani et al, 2018 ; Riba et al, 2001 ; Richards et al, 1977 ; Watts et al, 2017 ), and an enhancement of awe may persist beyond the acute experience ( Noorani et al, 2018 ).…”
Section: Potential Beneficial Synergy Of Psychedelics and Nature Contmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of awe has been linked to enhanced well-being ( Anderson et al, 2018b ; Dong and Ni, 2019 ; Rudd et al, 2012 ), life satisfaction ( Rudd et al, 2012 ), prosociality ( Bai et al., 2017 ; Piff et al, 2015 ; Sturm et al, 2020 ), and reduced negative affect ( Lopes et al, 2020 ), and mental distress ( Sturm et al, 2020 ), in addition to being associated with nature relatedness ( Bethelmy and Corraliza, 2019 ) and pro-environmental behaviour ( Wang and Liu, 2019 ; Zhao et al, 2018 ), all enduring effects associated with psychedelic use ( Gandy, 2019 ). Psychedelics have been found to elicit feelings of awe ( Griffiths et al, 2006 ; Hendricks, 2018 ; Noorani et al, 2018 ; Riba et al, 2001 ; Richards et al, 1977 ; Watts et al, 2017 ), and an enhancement of awe may persist beyond the acute experience ( Noorani et al, 2018 ).…”
Section: Potential Beneficial Synergy Of Psychedelics and Nature Contmentioning
confidence: 99%
“…For reviews of clinical studies with psychedelics see dos Santos et al (2018) . In studies looking at psychedelic administration amongst healthy populations, sustained increases across numerous measures of psychological well-being are observed (see reviews by Aday et al, 2020 ; Gandy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The items appear comparable to MEQ items focusing on a dynamic, variable, interactive process with the potential to seem strong and pleasant. The overlap with a stress index supports recommendations for extending psychedelic treatments to those who do not qualify for standard diagnoses of psychopathology (Gandy, 2019), many of whom might appreciate anxiolytic effects. Overlap scores ranged from 0.54 to 0.70.…”
Section: Ineffability Subscalementioning
confidence: 72%
“…Psychological research has also demonstrated that purported attributes of psychedelic experiences—such as increased feelings of gratitude—are themselves sensitive to the context of set and setting variables. Although gratitude has been referenced to explain the prosocial benefits of psychedelics (Gandy, 2019 ; Moreton et al, 2020 ), a recent paper by Tong and colleagues argues that gratitude can facilitate authoritarian obedience under specific context conditions. In their study, participants who were induced to feel gratitude were more likely to obey commands to grind worms in a grinder compared to those without gratitude priming.…”
Section: Power Trippingmentioning
confidence: 99%